2007
DOI: 10.1111/j.1439-037x.2007.00253.x
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and Biochemical Responses of Cowpea Genotypes to Water Stress Under Glasshouse and Field Conditions

Abstract: Five cowpea genotypes, Gorom local (Go), KVX61‐1 (KV), Mouride (Mo), Bambey 21 (B21) and TN88‐63 (TN), differing in their susceptibility to water stress, were studied under glasshouse and field conditions, to determine their physiological, biochemical and agronomic responses to water deficit at flowering stage. Effect of water deficit on leaf water potential (ψl), canopy temperature, gaseous exchange, leaf proline content, total protein and starch contents, maximal quantum yield (ϕp0) and yield components was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
49
0
5

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(62 citation statements)
references
References 22 publications
5
49
0
5
Order By: Relevance
“…Previous studies have shown that a dose of nitrogen at planting or coverage benefits the development of bean plants (Hungria et al, 2003;Xavier et al, 2008); hence the absence of the conventional treatment in this study, involving BNF alone, without any source of mineral nitrogen. In this study, seeding in pots with only sand as substrate was also avoided, since previous studies have shown that the bean is strongly hindered by this substrate without organic matter (Melo et al, 2005); moreover, this condition can easily lead to water deficit or high temperature in nodulated roots, which is harmful (Hamidou et al, 2007;Simões-Araújo et al, 2008). Under field conditions plants of all three cultivars exhibited similar behavior regarding gas exchange and photochemical efficiency for both treatments with BNF and not (Fig.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Previous studies have shown that a dose of nitrogen at planting or coverage benefits the development of bean plants (Hungria et al, 2003;Xavier et al, 2008); hence the absence of the conventional treatment in this study, involving BNF alone, without any source of mineral nitrogen. In this study, seeding in pots with only sand as substrate was also avoided, since previous studies have shown that the bean is strongly hindered by this substrate without organic matter (Melo et al, 2005); moreover, this condition can easily lead to water deficit or high temperature in nodulated roots, which is harmful (Hamidou et al, 2007;Simões-Araújo et al, 2008). Under field conditions plants of all three cultivars exhibited similar behavior regarding gas exchange and photochemical efficiency for both treatments with BNF and not (Fig.…”
Section: Discussionmentioning
confidence: 93%
“…This feature, a short period of peak photosynthesis in the preflowering phase, a common physiological behavior of bean, is perhaps the main reason that the culture responds to a small amount of mineral nitrogen while under BNF Hungary et al, 2003;Xavier et al, 2008;Pelegrin et al, 2009). Another determining factor for the low efficiency of BNF in bean is the occurrence of water stress (Figueiredo et al, 2007;Hamidou et al, 2007), even in Vigna, which is more tolerant of water shortage than Phaseolus (Pimentel and Hébert, 1999). This is especially true if these stressful conditions occur between vegetative and early reproductive stages, when the production of new nodules is stabilizing in cowpea (Senanayake et al, 1987), leading to low efficiency of BNF during the reproductive stage when a high amount of nitrogen is required by the leaves in legumes (Neves et al, 1982;Kaschuk et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The expression of these genes is differentially affected by the drought stress applied [2]. Heat-stress was associated with a decrease in the rate of growth and in the final length of barley and wheat coleoptiles [3,4] Osmotic adjustment is becoming increasingly recognised as an efficient drought tolerance mechanism in cultivated plants [5,6], exerting a positive effect-either directly or indirectly-on the productivity of plants that grow under drought conditions [7]. Genotypes with the ability to make osmotic adjustments produce greater yields; for example in chickpea [8,9], pea [10], sorghum [11,12], wheat [13,14], barley [15,16], sunflower [17] and potato [18] .…”
Section: Introductionmentioning
confidence: 99%
“…However, significant differences exist among cowpea genotypes in their response to drought (Watanabe et al 1997;Mai-Kodomi et al 1999). Stomatal closure has been identified as a common response to drought in cowpea (Ogbannaya et al 2003;Anya and Herzog 2004;Souza et al 2004;Hamidou et al 2007). 3 The Mozambican National Gene Bank has recently started collecting the country's national heritage of plant genetic resources.…”
Section: Cowpea [Vigna Unguiculata (L) Walp] Is An Important Proteimentioning
confidence: 99%